Uji Aktivitas Antibakteri dan Antifungi Kitosan dengan Pelarut Asam Askorbat - Angela Evelyna; Lia Amelia Tresna Wulan Sari; Margareth Juanita Aileen Lugito; Clairy Theodora (Jurnal Material Kedokteran Gigi, 2021)
Acrylic resins are widely used as removable denture baseplate. These resins need adequate cleaning and maintenance. One way to clean resin denture is by immersing it in a denture cleanser solution. Denture cleanser should have antibacterial and antifungal properties. Chitosan is a natural antibacterial and antifungal substance. Unfortunately, acetic acid used as solvent for chitosan solvent can cause toxicity to cells. Ascorbic acid can be used as an alternative solvent for chitosan with lower toxicity than acetic acid. The aim of this study is to test antibacterial and antifungal activity of chitosan solution in ascorbic acid for the use as resin acrylic cleanser. In this study we evaluate antibacterial and antifungal activity of chitosan solution in ascorbic acid as denture cleanser solution. Acrylic resin plates were contaminated with Streptococcus mutans and Candida albicans colonies and then were immersed in five different groups of solutions, aquadest as control group, ascorbic acid, 1%, 2%, and 3% chitosan solution in ascorbic acid. Antibacterial and antifungal activity test were examined by using diffusion method (Kirby-bauer). The results were analysed using statistical analysis.Antibacterial and antifungal activity test results show that the highest significant influence was observed in 1% chitosan group, showing 1,21x104 cfu/ml for Streptococcus mutans colonies and 4083 cfu/ml for Candida albicans colonies. The optimal percentage volume for adequate antibacterial and antifungal chitosan solution in ascorbic acid is 1%.